2007
DOI: 10.1104/pp.107.109686
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of a Fungal endo-Polygalacturonase Increases Plant Resistance to Pathogens and Reduces Auxin Sensitivity

Abstract: Polygalacturonases (PGs), enzymes that hydrolyze the homogalacturonan of the plant cell wall, are virulence factors of several phytopathogenic fungi and bacteria. On the other hand, PGs may activate defense responses by releasing oligogalacturonides (OGs) perceived by the plant cell as host-associated molecular patterns. Tobacco (Nicotiana tabacum) and Arabidopsis (Arabidopsis thaliana) plants expressing a fungal PG (PG plants) have a reduced content of homogalacturonan. Here, we show that PG plants are more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 76 publications
3
80
1
1
Order By: Relevance
“…To test whether the content of acidic HGA and/or the methylesterification status of HGA affects the susceptibility of plant cell walls to enzymatic saccharification, we analyzed Arabidopsis plants expressing a mutated version of the Aspergillus niger pgaII gene encoding a PG with reduced specific activity (PG plants) (11,12), and plants overexpressing AtPMEI-2, an endogenous inhibitor of PMEs (PMEI plants) (13,14). Leaf material from untransformed [wild-type (WT)] plants, from two independent lines (PG26 and PG57) with high levels of PG expression, from one line (PG106) with low levels of PG expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test whether the content of acidic HGA and/or the methylesterification status of HGA affects the susceptibility of plant cell walls to enzymatic saccharification, we analyzed Arabidopsis plants expressing a mutated version of the Aspergillus niger pgaII gene encoding a PG with reduced specific activity (PG plants) (11,12), and plants overexpressing AtPMEI-2, an endogenous inhibitor of PMEs (PMEI plants) (13,14). Leaf material from untransformed [wild-type (WT)] plants, from two independent lines (PG26 and PG57) with high levels of PG expression, from one line (PG106) with low levels of PG expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This can cause the production of small oligosaccharides and monosaccharides, which can act as elicitors of plant defense through signal transduction and transcription activation (Gille and Pauly, 2012). Ferrari et al (2007Ferrari et al ( , 2008 showed that transgenic plants expressing microbial PG were less susceptible to B. cinerea and had constitutively activated defense responses, possibly due to an increased accumulation of bioactive oligogalacturonides (OGs), elicitors perceived by the plant cell as danger-associated molecular patterns (DAMPs). It was demonstrated that OG-induced activation of basal resistance against fungal pathogens is mediated by molecular patterns independently of jasmonate-, salicylic acid-, and ethylene-mediated signaling but dependent on the expression of PAD3 (Ferrari et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since modification of plant cell wall structure may be critical for plant-pathogen interactions (Vorwerk et al, 2004;Lionetti et al, 2007;Ferrari et al, 2008), transgenic plants obtained in this study were challenged with pathogenic microorganisms. The susceptibility of Arabidopsis plants ectopically expressing AnAXE or AnRAE was assessed by inoculating leaves with B. cinerea conidia and subsequently evaluating symptoms 48 h post inoculation (hpi).…”
Section: Acetyltransferase-expressing Plants Have Increased Resistancmentioning
confidence: 99%
“…42, 81 It was proposed that Arabidopsis and tobacco overexpressing microbial AnPGII accumulate oligogalacturonide (OG) fragments, which serve as damage associated molecular patterns (DAMPs) acting in signaling the presence of cell wall damage caused by pathogens and leading to induction of disease resistance. Consistent with this hypothesis, PG-expressing plants showed enhanced constitutive defense responses, such as accumulation of UV-fluorescent metabolites, H2O2, β-1,3-glucanase and peroxidase and expression of defense-related genes.…”
Section: Post-synthetic Modifications Of the Cell Wall Affect Cwi Andmentioning
confidence: 99%
“…Consistent with this hypothesis, PG-expressing plants showed enhanced constitutive defense responses, such as accumulation of UV-fluorescent metabolites, H2O2, β-1,3-glucanase and peroxidase and expression of defense-related genes. 81 The size of OGs (usually between 10 and 15 glycosides) and their degree of methyl-and acetylesterification are important features for their ability to trigger plant defense responses. The de-esterification of OGs by overexpression of a fruit-specific PME in wild strawberry was required to elicit defense-related gene expression and induce plant resistance to B. cinerea.…”
Section: Post-synthetic Modifications Of the Cell Wall Affect Cwi Andmentioning
confidence: 99%